Infection with human rhinovirus 16 promotes enhanced IgE responsiveness in basophils of atopic asthmatics. Issue 10 (October 2014) - Agrawal, R.; Wisniewski, J.; Yu, M. D.; Kennedy, J. L.; Platts‐Mills, T.; Heymann, P. W.; Woodfolk, J. A.
Summary Background Rhinovirus and IgE act in concert to promote asthma exacerbations. While basophils are the principal cell type in the blood that is activated by IgE, their role in virus‐induced asthma episodes remains elusive. Objective To monitor IgE responsiveness in circulating basophils of rhinovirus‐infected atopic asthmatics during acute infection and convalescence. Methods The capacity for basophils to respond to IgE was assessed by testing the effects of allergen, or cross‐linking anti‐FcεRI and anti‐IgE antibodies, on surface TSLP receptor in 24‐hour PBMC cultures. Activation profiles of basophils from atopic asthmatics challenged intranasally with human rhinovirus 16 were monitored directly ex vivo or else in 24‐hour cultures, at baseline (day 0), and then at days 4 and 21 post‐challenge. Results Basophils in atopic asthmatics, but not in non‐atopic controls, upregulated TSLP receptor upon IgE receptor ligation. The magnitude of this response was correlated with the proportion of serum total IgE that was allergen‐specific (r = 0.615, P < 0.05). Following rhinovirus infection, all subjects developed nasal symptoms that peaked 3–5 days after viral challenge. Basophils displayed maximal IgE responsiveness 3 weeks post‐challenge as judged by TSLP receptor levels in 24‐hour cultures. No significant change in total IgE or specific IgE antibodies was detected during rhinovirus infection. By contrast, levels of IgE receptor‐associated spleen tyrosine kinase, Syk, were increased on day 4 (P < 0.05), and elevated levels were also detected three weeks post‐challenge. Conclusions and Clinical Relevance Circulating basophils display increased IgE responsiveness 3 weeks after rhinovirus infection in atopic asthmatics. This observation, coupled with increased expression of Syk, implicates basophils in promoting, or else prolonging, rhinovirus‐induced inflammation in atopic asthmatics.